"Analisis Sistematis Literatur tentang Transformasi Pelatihan dan Pengembangan Guru sebagai SDM pada Lembaga Pendidikan di Era Digital" - Yulianti Farida; Ida Rindaningsih (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
The digital era has brought significant changes to human resource development and training (HRD), especially in educational institutions. The transformation from conventional methods to technology-based approaches, such as e-learning, webinars, and interactive applications, has opened opportunities to enhance the efficiency and flexibility of training programs. This article examines the transformation of HRD training in the digital era using the Systematic Literature Review (SLR) method to analyze relevant literature. The findings reveal that digital-based training not only enhances technical skills but also supports the development of professional, pedagogical, and social competencies of educators.However, this transformation faces several challenges, including digital literacy gaps, limited infrastructure, and data security risks. Therefore, strategic approaches are needed, such as improving digital literacy, investing in technological infrastructure, and implementing secure data management. By addressing these challenges, educational institutions can create adaptive, innovative, and competitive human resources that meet the demands of the digital age. This article provides a framework for designing responsive and relevant HRD training programs amidst technological advancements.